THE IMPACT OF DROUGHT ON YIELD POSITION OF THE GROUP OF ENTERPRISES FROM AGRICULTURE SECTOR - Sonja, Đuričin; Duško, Bodroža (Economics of Agriculture, 2013)
Starting from the fact that the amount and distribution of precipitations and the intensity of drought, considering the condition and extant of the use of irrigation systems, result in relatively low and unstable level of crop yields, the starting hypothesis of the research is that the agro meteorological trends in the period 2007-2010 influenced the yield position of the analyzed agricultural sector of Serbia. The aim of the paper is to determine the level of impact of agro meteorological trends on yield position of the group of business entities in the prevailing market conditions. The subject of the research refers to the analysis of the operation of the Serbian agricultural sector under the following activity code 011-cultivation of crops, plants and gardening. As the main source of data, the paper uses the summary financial statements of a group of business entities from agricultural sector under the activity code 011 and agro meteorological data for the period 2007-2010. By using the qualitative and quantitative methods of financial statement analysis and the synthesis of research results, the conclusion has been made that agro meteorological conditions in the observed period of time and under the existing market conditions had a significant impact on the worsening of yield position of the Serbian agricultural sector under survey.